Social transformations in Algerian desert cities and the problem of identity: Socio-anthropological study in the city of Djanet - amrani, zineb; mechta, yacine (Journal of Social Sciences and Humanities, 2025)
The subject of this research paper deals with the problem of social transformations witnessed by Algerian desert cities and their relationship to the social identity of the inhabitants of these cities, as the urban context of desert cities in general and the city of Djanet in particular was characterized by continuous and rapid development, especially in recent years, including the socio-economic and urban dimension. This shift and change is explained by a set of factors that we limited to mentioning political, educational and the demographic factor.